2020
DOI: 10.1038/s41394-020-0275-8
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 and spinal cord injury and disease: results of an international survey

Abstract: Study design An online survey.Objectives To query the international spinal cord medicine community's engagement with and response to the novel coronavirus (COVID-19) pandemic and to assess pandemic-specific information needs and patient concerns. Setting An international collaboration of authors and participants. Methods Two near-identical surveys (one English and one Spanish language) were distributed via the internet. Responses from those questions shared between the surveys were pooled then analyzed; four q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
74
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 59 publications
(75 citation statements)
references
References 7 publications
1
74
0
Order By: Relevance
“…In an international survey of health care professionals (n = 783) who care for individuals with SCI, 10.3% reported their patients with COVID-19 had increased spasticity, 6.9% reported that their patients had rigors, and 6.9% reported that their patients had been asymptomatic. This early report warrants special consideration during triage of people with SCI for suspected COVID-19 [9].…”
mentioning
confidence: 90%
“…In an international survey of health care professionals (n = 783) who care for individuals with SCI, 10.3% reported their patients with COVID-19 had increased spasticity, 6.9% reported that their patients had rigors, and 6.9% reported that their patients had been asymptomatic. This early report warrants special consideration during triage of people with SCI for suspected COVID-19 [9].…”
mentioning
confidence: 90%
“…As Covid-19 is a novel viral respiratory infection, its epidemiology and clinical course among people with SCI are yet unknown. However, recently the first survey has been published which addresses COVID-19-related practices and adaptations among health care professionals working with individuals with SCI [11]. So far, only one case of Covid-19 infection with SCI has been reported [12].…”
Section: Introductionmentioning
confidence: 99%
“…Health services should also support patient and family health literacy by providing pandemic information in age appropriate forms, multiple languages and diverse formats (67,82). The need to increase education and health literacy speci cally about Covid-19 in the community is a current priority (83,84).…”
Section: Communicationmentioning
confidence: 99%